An Imperata Cylindrical Flowers-Shaped Porous Graphene Microelectrode for Direct Electrochemistry of Glucose Oxidase. Issue 7 (31st March 2015) - Shi, Yujie; Li, Xuan; Ye, Minghui; Hu, Chuangang; Shao, Huibo; Qu, Liangti
Abstract : A novel flowers-shaped porous active graphene microelectrode has been fabricated by directly electrochemical assembly and reduction of graphene oxide on platinum (Pt) wire with a diameter of 250 μm. The flowers-shaped graphene microelectrode was characterized by SEM, XRD and electrochemical techniques. Results showed that the flowers-shaped graphene microelectrode created a favorable microenvironment for the GOD. The as prepared graphene microelectrode exhibited excellent electron transfer properties for GOD with the rate constant ( k s ) of 2.18 s −1 and achieved the direct electrochemistry of GOD. It is notable that the glucose biosensor of GOD@flowers-shaped graphene microelectrode showed two linear ranges in 8.0–148.0 μM with the sensitivity of 267.34 μA mM −1 cm −2 and in 148.0–430.6 μM with the sensitivity of 38.15 μA mM −1 cm −2 for detecting glucose. Furthermore, the biosensor possessed strong anti-interference, remarkable stability and appreciable reproducibility for the sensitive determination of glucose. It would also be extended to other analogous enzymes and bioactive molecules for various biological and electrochemical applications.